2001
DOI: 10.1002/1099-0690(200111)2001:22<4223::aid-ejoc4223>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Density Functional and ab initio Quantum Chemical Study of the Brandi Reaction

Abstract: The Brandi reaction is the transformation of spiro[cyclopropane-1,5Ј-isoxazolidines] into tetrahydropyridones under thermal conditions. According to calculations performed by the restricted and unrestricted density functional theory and post-Hartree−Fock single-and multireference methods of ab initio quantum chemistry, the reaction proceeds through two biradical intermediates. These intermediates result from the homolytic cleavage of the N−O bond of the isoxazolidine ring in the first step, and the homolytic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 10 publications
2
26
0
Order By: Relevance
“…[2][3][4] Homologous 5-spirocyclobutane-isoxazolidines 6, obtained by 1,3-dipolar cycloadditions of nitrones 4 to methylenecyclobutane (5) (Scheme 2), undergo thermal rearrangement under harsher conditions, [5] as validated by a recent computational study. [6] In particular, the activation energy for the rate-determining step of the rearrangement, [ ane-isoxazolidines, which requires higher energy than protonation at nitrogen, but can trigger the proposed process without any energy barrier. The N-protonated derivatives could rearrange to give oxazaspirooctane, with enlargement of the spirocyclobutane ring, but this process, owing to its high energy barrier, cannot compete with the reaction channel promoted by oxygen protonation and, in fact, is not experimentally observed.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4] Homologous 5-spirocyclobutane-isoxazolidines 6, obtained by 1,3-dipolar cycloadditions of nitrones 4 to methylenecyclobutane (5) (Scheme 2), undergo thermal rearrangement under harsher conditions, [5] as validated by a recent computational study. [6] In particular, the activation energy for the rate-determining step of the rearrangement, [ ane-isoxazolidines, which requires higher energy than protonation at nitrogen, but can trigger the proposed process without any energy barrier. The N-protonated derivatives could rearrange to give oxazaspirooctane, with enlargement of the spirocyclobutane ring, but this process, owing to its high energy barrier, cannot compete with the reaction channel promoted by oxygen protonation and, in fact, is not experimentally observed.…”
Section: Introductionmentioning
confidence: 99%
“…Of special concern is the regioselectivity of cycloadditions of MCP 74 and N ‐oxides 78 ,, since 4‐spiro adducts 80 are incapable of the described rearrangement. The transformations usually require high temperatures (up to flash vacuum thermolysis) and the suggested initial homolytic N−O bond cleavage is supported by quantum calculations . The major rearrangement pathway is the ring enlargement to piperidinones 82 (known as Brandi‐Guarna rearrangement), with opening to enamines 84 often observed as a side process.…”
Section: Transformations Of Small Ring Annelated Isoxazolidinesmentioning
confidence: 95%
“…The homologous 5‐spirocyclobutaneisoxazolidines 26 , obtained by 1,3‐DC of nitrones with methylenecyclobutane ( 25 , MCB ) (Scheme 14), undergo the thermal rearrangement under harsher conditions, [21] as predicted by a computational study [22] . This study showed that the activation energy of the rate determining step for the rearrangement, i. e. the cleavage of the N−O bond in 5‐spirocyclobutaneisoxazolidines, is ca 14 kcal/mol higher than in the 5‐spirocyclopropane derivatives 1 (Scheme 1).…”
Section: Comparison Between 5‐spirocyclopropane‐ and 5‐spirocyclobutamentioning
confidence: 99%
“…The 5‐spirofused cyclopropyl moiety, instead, induces a peculiar selectivity in the rearrangement of isoxazolidines, either under neutral [1,22,26] or acidic conditions. Gandolfi, [24,27] as shown before, had preliminarily computationally justified this behaviour through an N−O cleavage of the protonated isoxazolinium ion followed by two possible pathways, a concerted cleavage of the two bonds of the cyclopropane ring, or a stepwise (diradical) fragmentation of the two bonds (Figure 1).…”
Section: Computational Studiesmentioning
confidence: 99%